On file sharing with indirect Network effects between concert ticket sales and music recordings - Ralf Dewenter; Justus Haucap; Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
This paper analyses the interdependency between the market for music recordings and concert tickets, assuming that there are positive indirect network effects both from the record market to ticket sales for live performances and vice versa. In a model with two interrelated Hotelling lines prices in both markets are corrected downwards when compared to the standard Hotelling model. Also, file sharing has ambiguous effects on firms' profitability. As file sharing can indirectly increase demand for live performances overall profits can either increase or decrease, depending on the strength of indirect network effects. Finally, file sharing may induce firms to switch from the traditional business model with two separate firms to an integrated business model where one agency markets both records and concerts (so-called 360 degree deals).
Keywords: L13; L82; Z10; 330; Musikwirtschaft; Internet; Event-Marketing; Network Externalities; Hotelling Modell; Theorie